Development of Inquiry-Based Science Virtual Laboratory for Improving Student Thinking Skill of Junior High School - Asri Widowati; Sabar Nurohman; Didik Setyowarno (Jurnal Pendidikan Matematika dan Sains, 2017)
This research  was conducted to produce inquiry-based science virtual laboratory that was eligible for developing students' thinking skills in science learning, and  to determine the effectiveness of a virtual laboratory to develop students' thinking skills. The research method was Research and Development (R D), by pointing to Four D models and Borg Gall Model. There were 4 main phases (define, design, develop, disseminate) and additional phases (preliminary field testing, main product revision, main field testing, and operational product revision).  Research subjects were junior high school students of 7rd class. The instruments used included product validation questionnaire, observation sheet of thinking skill, and test. For the validation of data and student response data were analyzed descriptively; and test results were analyzed by paired-t test. The results showed that the inquiry-based science virtual laboratory product was considered as excellent by expert and teacher and it was appropriate to use in science learning. Its effectiveness to increase students' thinking skills was showed by by significant  value=0,000 from t-paired test..